First-principles study of the structural, phonon, elastic, and thermodynamic properties of Al3Ta compound under high pressure - Leini, W.; Zhang, T.; Wu, Z.; Wei, N. (Condensed Matter Physics, 2018)
We have investigated the phonon, elastic and thermodynamic properties of L1₂ phase Al₃Ta by density functional theory approach combining with quasi-harmonic approximation model. The results of phonon band structure shows that L1₂ phase Al₃Ta possesses dynamical stability in the pressure range from 0 to 80 GPa due to the absence of imaginary frequencies. The pressure dependences of the elastic constants Ci j, bulk modulus B, shear modulus G, Young’s modulus Y, B/G and Poisson’s ratio ν have been analysed. The elastic constants are satisfied with mechanical stability criteria up to the external pressure of 80 GPa. The results of the elastic properties studies show that Al3Ta compound possesses a higher hardness, improved ductility and plasticity under higher pressures. Further, we systematically investigate the thermodynamic properties, such as the Debye temperature Θ, heat capacity Cp, and thermal expansion coefficient α, and provide the relationships between thermal parameters and pressure.